Traditional knowledge and use of wild edible plants in Sidi Bennour region (Central Morocco) - Aboukhalaf, Abdelghani; Tbatou, Manal; Kalili, Adil; Naciri, Kaoutar; Moujabbir, Sara; Sahel, Khadija; Rocha, João Miguel; Belahsen, Rekia (Ethnobotany Research and Applications, 2022)
Background: This study aimed to protect the knowledge related to the traditional uses of wild plant resources which constituted untapped potential as dietary supplements and therapeutic products Methods: An ethnobotanical survey based on the Semi-Structured Interview method was carried out among the Sidi Bennour region from February 2019 to February 2020. Results: The results showed that a total of 56 plant species representing 56 genera and 27 families were used to make different food dishes and in the treatment of various diseases. The most cited wild edible plants (WEPs) families were Asteraceae (16%). The leaves (38%) and stems (32%) were the most parts commonly used in food. Four utilization categories were cited, vegetables, for seasoning, as a drink, and Other (plants used to decorate or flavor traditional dishes). The use of these WEPs as vegetables was the most cited mode of consumption (37.5%) by the local population. The leaves were the most commonly used part (35%) for medicinal uses of WEPs. Decoction (27.27%) was the most common method of preparing traditional medicines. The majority of preparations were administered orally (80.25%). The study results showed also that local people have sufficient information on the safe use of WEPs. Conclusions: The present study demonstrated that the people of the Sidi Bennour region, hold rich traditional knowledge of a large number of WEPs, however, the study population underlined the sharp decline in the consumption of most of the species recorded consequently the detailed documentation may effectively prevent knowledge loss through time. Keywords: ethnobotanical survey, Wild edible plants, relative frequency index of citation, phytotherapy, beqoula, Sidi Bennour, Morocco